MiR-146b is a regulator of human visceral preadipocyte proliferation and differentiation and its expression is altered in human obesity - Chen, Ling; Dai, Yong-Mei; Ji, Chen-Bo; Yang, Lei; Shi, Chun-Mei; Xu, Guang-Feng; Pang, Ling-Xia; Huang, Fang-Yan; Zhang, Chun-Mei; Guo, Xi-Rong (Molecular and cellular endocrinology, 2014)
•MiR-146b, highly expressed in mature adipocytes while lowly in human mesenchymal stem cells and visceral preadipocytes.•Gain-and loss-of-function studies indicated that miR-146b could affect visceral adipogenesis.•MiR-146b in human visceral adipocytes could inhibit both of KLF7 mRNA and protein levels.•Firefly luciferase reporter assay proved that KLF7 was a direct target of miR-146b in human visceral adipocytes.•MiR-146b expression was significantly altered in adipose tissues of human obesity and DIO mice. Visceral obesity is an independent risk factor for metabolic syndrome, and abnormal fat accumulation is linked to increases in the number and size of adipocytes. MiR-146b was a miRNA highly expressed in mature adipocytes while very lowly expressed in human mesenchymal stem cells (hMSCs) and human visceral preadipocytes (vHPA). In this paper, we mainly focused on the roles of miR-146b in adipogenesis. We found miR-146b could inhibit the proliferation of visceral preadipocytes and promote their differentiation. MiR-146b in human visceral adipocytes inhibited the expression of KLF7, a member of the Kruppel-like transcription factors, as demonstrated by a firefly luciferase reporter assay, indicating that KLF7 is a direct target of the endogenous miR-146b. MiR-146b expression was significantly altered in visceral and subcutaneous adipose tissues in human overweight and obese subjects, and in the epididymal fat tissues and brown fat tissues of diet-induced obese mice. Our data indicates that miR-146b may be a new therapeutic target against human visceral obesity and metabolic dysfunction.